Increased cortical thickness in a frontoparietal network in social anxiety disorder. Issue 7 (13th September 2013) - Brühl, Annette Beatrix; Hänggi, Jürgen; Baur, Volker; Rufer, Michael; Delsignore, Aba; Weidt, Steffi; Jäncke, Lutz; Herwig, Uwe
Abstract Social anxiety disorder (SAD) is the second leading anxiety disorder. On the functional neurobiological level, specific brain regions involved in the processing of anxiety‐laden stimuli and in emotion regulation have been shown to be hyperactive and hyper‐responsive in SAD such as amygdala, insula and orbito‐ and prefrontal cortex. On the level of brain structure, prior studies on anatomical differences in SAD resulted in mixed and partially contradictory findings. Based on previous functional and anatomical models of SAD, this study examined cortical thickness in structural magnetic resonance imaging data of 46 patients with SAD without comorbidities (except for depressed episode in one patient) compared with 46 matched healthy controls in a region of interest‐analysis and in whole‐brain. In a theory‐driven ROI‐analysis, cortical thickness was increased in SAD in left insula, right anterior cingulate and right temporal pole. Furthermore, the whole‐brain analysis revealed increased thickness in right dorsolateral prefrontal and right parietal cortex. This study detected no regions of decreased cortical thickness or brain volume in SAD. From the perspective of brain networks, these findings are in line with prior functional differences in salience networks and frontoparietal networks associated with executive‐controlling and attentional functions. Hum Brain Mapp 35:2966–2977, 2014. © 2013 Wiley Periodicals, Inc.